(untitled) (Journal of Economic Research & Business Administration, 2016)
Kazakhstani model of the bank’s restructuring was carried out in two ways: firstly, the restructuring of the banking system in general, and sec ondly, an individual bank restructuring to avoid bankruptcy. Analysis of the effectiveness of Kazakhstan’s model of an individual bank restructuring was carried out on the basis of the coefficient analysis of three conditional periods – precrisis (2007), before restructuring (2009) and after restructur ing (2012). Measuring the effectiveness of the restructuring of the banking sector as a whole is considered in two periods: the precrisis (2007) and the most recent data (2014).